How Anterior Cruciate Ligament Injury was averted during Knee Collapse in a NBA Point Guard - Nathan D Schilaty; Nathaniel A Bates; Aaron J Krych; Timothy E Hewett (Annals of Musculoskeletal Medicine - Peertechz Publications, 2017)
Non-contact anterior cruciate ligament (ACL) injuries occur with rapid decelerations and pivoting. A recent injury to a high-level National Basketball Association (NBA) player demonstrated neuromuscular control and injury-sparing mechanisms that resulted in only minor ligament injury to the medial collateral ligament. We analyzed biomechanical mechanisms via publically available orthogonal 2-D video to demonstrate how this potential ACL injury was averted. Analysis of the knee injury mechanismdemonstrated that the NBA player experienced low ground reaction force, high sagittal plane fl exion, and maintenance of frontal plane stability with neuromuscular control. The outcome of these factors inhibited dynamic valgus collapse of the knee throughout the fall, avoiding ACL injury - a potentially career-altering injury. Many athletes, professional and recreational, will be subjected to similar mechanisms of injury and will have improved outcomes if they can successfully utilize preventive strategies of neuromuscular control to limit injury mechanisms. Pubmed link:https://www.ncbi.nlm.nih.gov/pubmed/28603786